2021
DOI: 10.3390/nano11081922
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tomato Infecting Viruses That Co-Isolate with Nanovesicles Using a Combined Proteomics and Electron-Microscopic Approach

Abstract: Plant-derived nanovesicles (NVs) have attracted interest due to their anti-inflammatory, anticancer and antioxidative properties and their efficient uptake by human intestinal epithelial cells. Previously we showed that tomato (Solanum lycopersicum L.) fruit is one of the interesting plant resources from which NVs can be obtained at a high yield. In the course of the isolation of NVs from different batches of tomatoes, using the established differential ultracentrifugation or size-exclusion chromatography meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…In our recent studies, we observed that state-of-the-art EV purification from apoplastic fluids leads to impure EV isolates containing additional co-purified apoplastic substances [47]. This finding aligns with recent debates discussing the pitfalls of current plant EV research methods and the need for standardization, with different contamination risks reported for different plant EV separation and characterization methods [33,40,46]. To avoid such pitfalls that may lead to false conclusions, we performed a stringent digestive treatment of EV isolates to degrade extravesicular proteins and RNAs before in vitro treatment of F. graminearum with plant EVs.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In our recent studies, we observed that state-of-the-art EV purification from apoplastic fluids leads to impure EV isolates containing additional co-purified apoplastic substances [47]. This finding aligns with recent debates discussing the pitfalls of current plant EV research methods and the need for standardization, with different contamination risks reported for different plant EV separation and characterization methods [33,40,46]. To avoid such pitfalls that may lead to false conclusions, we performed a stringent digestive treatment of EV isolates to degrade extravesicular proteins and RNAs before in vitro treatment of F. graminearum with plant EVs.…”
Section: Resultssupporting
confidence: 83%
“…thaliana in vitro. The impurity of plant EV isolates raised concerns about the reliability of findings and their interpretation [33,46]; we thus performed rigorous digestive treatments of EV isolates before F. graminearum in vitro testing. Encouraged by our previous finding that drop inoculation of barley EVs on F. graminearum cultures grown on solid agar plates caused an increase in purple pigmentation, indicative of the stress-induced premature formation of fruiting bodies [48], we expected to observe similar effects in liquid cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, plant-derived nanovesicles (PDNVs) have emerged due to their perspective towards biomedical and nanotechnological applications. They have been isolated from many homogenized plants and fruit juices, including tomato [ 1 , 2 ], citrus species [ 3 , 4 , 5 ], strawberry [ 6 , 7 ] and ginseng [ 8 , 9 ], just to mention some. In this paper, we use PDNVs as an umbrella term to refer to all kind of nano-sized particles, nanolipids, exosomes, nanovectors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have reported the isolation and characterization of NVs from tomato ( Solanum lycopersicum L.) fruit [ 1 , 2 ]. Tomatoes are healthy, versatile and an essential fruit of the Mediterranean diet with associated health benefits, including improved antioxidant defense and reduced risk of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Samples of SCPs were prepared using Vitrobot Mark IV (Thermo Fisher Scientific, Waltham, MA, USA). Quantifoil ®® R 2/2, 200 mesh holey carbon grids (Quantifoil Micro Tools GmbH, Großlöbichau, Germany) were glow-discharged for 60 s at 20 mA and positive polarity in the air (GloQube ®® Plus, Quorum, Laughton, UK) [ 55 ]. Conditions were set at 4 °C, 100% relative humidity, blot time: 5 s, and blot force: 4.…”
Section: Methodsmentioning
confidence: 99%